The Effect of Profitability Liquidity and Company Size on Firm Value in Food and Beverage Companies on the Indonesia Stock Exchange (IDX) for the Period 2018-2022 - Vinasti Vinasti; Nanang Qosim; Zulfikar Jakaputera Djalamang; Akhmad; Nurapiah (PT. Anagata Sembagi Education, 2024)
This study aims to determine the effect of profitability liquidity and company size on firm value in food and beverage companies on the Indonesian stock exchange (IDX) for the period 2018-2022. The data used in this study are quantitative data. The population in this study were 33 companies, and the samples used in this study were 12 companies. The observation period was carried out for 5 years, starting from 2018-2022. The data used is secondary data, namely data obtained directly in the form of financial reports on the site www.idx.co.id. The data analysis technique used uses statistical analysis, namely: The results of the study simultaneously show that profitability liquidity and company size have a significant effect on firm value in food and beverage companies listed on the Indonesian stock exchange (IDX) for the period 2018 - 2022. Then the partial research results profitability has no significant effect on firm value and liquidity has a negative and insignificant effect on firm value. While company size has a negative and significant effect on firm value.